Globalizing Genomics: The Origins of the International Nucleotide Sequence Database Collaboration - Stevens, Hallam (2018)
Genomics is increasingly considered a global enterprise – the fact that biological information can flow rapidly around the planet is taken to be important to what genomics is and what it can achieve. However, the large-scale international circulation of nucleotide sequence information did not begin with the Human Genome Project. Efforts to formalize and institutionalize the circulation of sequence information emerged concurrently with the development of centralized facilities for collecting that information. That is, the very first databases build for collecting and sharing DNA sequence information were, from their outset, international collaborative enterprises. This paper describes the origins of the International Nucleotide Sequence Database Collaboration between GenBank in the United States, the European Molecular Biology Laboratory Databank, and the DNA Database of Japan. The technical and social groundwork for the international exchange of nucleotide sequences created the conditions of possibility for imagining nucleotide sequences (and subsequently genomes) as a “global” objects. The “transnationalism” of nucleotide sequence was critical to their ontology – what DNA sequences came to be during the Human Genome Project was deeply influenced by international exchange.